2015
DOI: 10.1007/s00464-015-4223-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of robotic single-incision and traditional single-incision laparoscopic cholecystectomy

Abstract: While RSILC can be safely performed, it is associated with longer operative times and greater cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…Two comparative studies reported on costs [173, 174]. One study reported comparable costs of instruments ($1268 for SIRC and $1282 for SILC).…”
Section: Resultsmentioning
confidence: 99%
“…Two comparative studies reported on costs [173, 174]. One study reported comparable costs of instruments ($1268 for SIRC and $1282 for SILC).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies also reported that robotic cholecystectomy required more medical cost than laparoscopic cholecystectomy, and there may be differences in the total medical cost among other countries. 17,18 As mentioned before, the costs of the routine preoperative examinations and hospital fees are the same between robotic and laparoscopic groups. 9 Efforts will be needed to reduce the surgery-related costs in SIRC through the development of various robotic systems and their competitions.…”
Section: Discussionmentioning
confidence: 90%
“…Similar to the present results, previous studies demonstrated the safety and feasibility of SIRC compared with SILC or 3PLC. [16][17][18] Although it was difficult to obtain a critical view of safety (CVS) in some SILC cases because of limitation of cross movement of instruments, the CVS was obtained in all the cases and then the surgery was proceeded.…”
Section: Discussionmentioning
confidence: 99%
“…6 For single-incision robotic cholecystectomy (SIRC), there are debates regarding operation time, with some authors reporting a longer operation time for SIRC than SILS (98 vs 68 min, p<0.001). 7 Conversely, a significant difference in operation time was reported for RSSC (62 min) and SILS (83 min). 8 A recent multicenter study showed a short operative time of RSSC of 52 min with a decreasing trend after 55~85 cases.…”
mentioning
confidence: 99%
“…In the present study, the operation time was 97.2 min, the console time was 49 min, and the docking time was 10 min, which is similar to other reports. 7,10 The authors also described a decreasing trend of console time with accumulation of experience, indicating the potential to overcome the long operation time of SIRC.…”
mentioning
confidence: 99%